The Role of Profitability and Leverage on Corporate Social Responsibility Disclosure in Mining Company Indonesia - Kartika Pratiwi Puteri; Restu Pebiani; Maria Lusiana Yulianti; Annisa Fitri Anggraeni; Khania Puteri Hadiyani (Greenation International Journal of Economics and Accounting, 2023)
Today, companies are required to compete, in order to maintain their business. Companies are required to have a professional management structure in order to continue to survive and develop in this digital era. In the business world, companies are considered to only aim to get the maximum profit, even though companies need to pay attention to the impacts arising from their business activities, because the development of the business world focuses on the company's environment. The company is expected not only to prioritize the interests of management and owners of capital but also employees, consumers, society and the environment. This study aims to analyze the influence of profitability and leverage on CSR disclosure at mining companies in Indonesia. Profitability in this study is proxied by ROA (Return On Assets), Leverage is proxied by DER (Debt to Equity Ratio) and CSR Disclosure is proxied by GRI 4.0 index measurement. The target population in this study were 63 mining companies listed on the IDX for the 2022 period. However, for the research sample, only 51 companies passed the criteria, namely issuing annual reports and sustainability reports in this period. The results of the study show that profitability and leverage affect CSR disclosure in mining companies in Indonesia.